L’empathie en EHPAD : une pédagogie interculturelle à destination des aidants - Lefelle, Marie (Neofilolog, 2023)
Assistance to the elderly remains a sector in high demand which is interested in recruiting people from migrant backgrounds. Language training for these learners in particular raises new questions for the language educator because beyond the language aspect, there is also the cultural component essential to practice. Indeed, how can we as language educator adressed a empathy culturally situated in the relationship with the elderly. Empathy is expressed differently depending on the culture present, through communication or gesture or a mixture of both. Through a collection of data, we will illustrate the importance of concepts such as empathy in situations involving end-of-life. The corpus will serve as a basis for reflection on the cultural component necessary for the care of the elderly and on the educational solutions envisaged in the training of carers of migrant background.